Enzymatic measurement of choline-containing phospholipids in bile. - D Gurantz (Journal of Lipid Research, 1981)
An enzymatic method, previously used to determine choline-containing phospholipids in serum, was applied to the estimation of phospholipid concentration in bile. The method combines three enzymatic reactions: a) release of choline by phospholipase D; b) choline oxidation by choline oxidase, a reaction which generates hydrogen peroxide; and c) formation of a red quinone dye by peroxidase. The method is an endpoint, spectrophotometric determination. It is simple, sensitive, and reproducible. Accuracy was demonstrated both by linear recoveries of the choline-containing phospholipids in bile and a good correlation with a chemical determination. No interferences by bile acids and/or cholesterol were observed; bile pigment interference was removed by bleaching with white light. This method which determines lipid choline is simpler than the widely used chemical determination of lipid phosphorus.